Managing social media in libraries : finding collaboration, coordination and focus - Swanson, Troy A.; ScienceDirect eBooks (Oxford : Chandos Pub., 2012)
"This book is an argument for making social media fit your library. Managing Social Media in Libraries explores the developing information environment, collaboration among library organizations, and ways social media may convert the loose connections between library staff members into meaningful cooperation. The book takes librarians beyond the mechanics of using social media, and establishes a framework to move library managers and leaders toward making social media effective. The argument here is that social media in your library must make sense for your library. It is about weighing needs and resources and considering how staff members work as an organization, because this book is not really about technology at all. It is about people, interaction and engagement."--Publisher.
Where have we been with social media? -- Library organizations as loosely-coupled systems -- Social media in loosely-coupled systems -- Defining a purpose -- Connecting social media tools to the organization -- Integrating with standard websites -- Leadership : big ideas do not have to be that big.
Includes bibliographical references (pages 159-163) and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Social media -- Management; Social media; Libraries -- Communication systems; Organizational behavior; Communication in organizations; Online social networks -- Library applications; Communication in library administration; Communication in library science; LITERARY CRITICISM -- Books & Reading; Electronic books